Plasma bubble imaging by single-frequency GNSS measurements - Christovam, Ana L. [UNESP]; Prol, Fabricio S.; Hernández-Pajares, Manuel; Camargo, Paulo O. [UNESP] (Springer Nature, 2023)
Our investigation aims to answer if it is possible to detect plasma bubbles using single-frequency measurements of the Global Navigation Satellite System (GNSS). In this regard, we show a methodology based on a regional model to calibrate GNSS single-frequency measurements and derive ionospheric maps showing plasma bubbles in one of the most challenging conditions, the Brazilian region. Simultaneous observations of all-sky images at Cachoeira Paulista (22.7°S, 45.0°W), São João do Cariri (7.4°S, 36.5°W) and Boa Vista (2.8°N, 60.7°W) were used to compare the plasma bubbles structures. The results were validated by the comparison between airglow and total electron content (TEC) single-frequency maps in terms of keograms and drift velocities of the ionospheric plasma bubbles. Plasma bubbles were successfully observed by mapping TEC single-frequency. The rate of success in detecting the plasma bubbles with single-frequency TEC data was 65% when using keograms. In addition, in regions with good GNSS coverage, such as Cachoeira Paulista and São João do Cariri, it was easier to detect the plasma bubbles. The velocities of plasma bubbles were also obtained with good agreement in comparison with the velocities estimated using airglow data. For São João do Cariri, the mean drift velocities estimated with airglow data were 117.10 m/s whereas with TEC data were 117.94 m/s. Therefore, the results revealed the proposed method as an efficient tool for mapping the ionospheric plasma bubbles and computing their drift velocities. This technique provides new opportunities, in particular for ionospheric sounding, since the number of low-cost GNSS receivers continues growing.
Keywords: Airglow images; Ionosphere; Plasma bubbles; Single-frequency; Spherical harmonics; TEC